El desarrollo territorial en la parroquia Vilcabamba: un análisis sinergético, año 2023 - Rodríguez Castillo, Kerly Stephany (2024)
The present Curricular Integration Work called "The territorial development of the Vilcabamba parish: a synergistic analysis, year 2023" was carried out taking into account each of the phases of the investigative process, in the same way, its execution based on the guidelines established in the Academic Regulations of the National University of Loja. This research starts with the objective of analyzing the territorial development of the parish of Vilcabamba, based on the forms of capital that contribute to it. Therefore, in order to comply with this, it was identified that there are several forms of capital that make up territorial development, with the interest of focusing on the most outstanding ones, which are: economic, social, cultural, human and institutional; the joint interaction of these capitals makes up what is called synergistic capital. It is relevant to focus on social and cultural capital due to the loss of existing cultural identity, this is due to the presence of residents who directly influence the younger generations with their new cultures. These forms of capital are essential to build a solid base for territorial development, as they influence community collaboration, cultural identity and the well- being of the inhabitants. The results are presented thanks to the methodologies applied, where on the one hand the review of the previous literature and on the other the surveys, Interviews and observation sheets carried out contributed; after identifying the socio- cultural aspects that have been lost, a concrete proposal is established to maintain social and cultural capital. Subsequently, it moves on to the discussion where the most relevant results of the research are highlighted, corroborating with the previous research, indicating in detail the factors that influence the loss of cultural identity within the parish. Finally, the relevant conclusions and recommendations are presented.